Excavations at Pasargadae: Third Preliminary Report - Stronach, David
Summary of the 1963 Campaign – Architectural Surveys of the Gatehouse, the Audience Hall and the Private Palace – Architectural Survey of the Zendan – Function of the Zendan – Excavations on the Citadel – Period I (c. 550-522 B.C.) – Period II (c. 522-280 B.C.) – The Plan of the Period II Defences – The Summit Terrace – Period III – Period IV – The Sacred Precinct – The Palace Area – The Bridge – The Garden Pavilion – The Treasure. Catalogue – PI. V: The Daiva Inscription; pl. VIe: Fragment of Old Persian Inscription Found on Northern Edge of Palace Area.